A systematic review of higher-risk myelodysplastic syndromes clinical trials to determine the benchmark of azacitidine and explore alternative endpoints for overall survival. (May 2021) - Garcia, Jacqueline S.; Swords, Ronan T.; Roboz, Gail J.; Jacoby, Meagan A.; Garcia-Manero, Guillermo; Hong, Wan-Jen; Yang, Xiaoqing; Zhou, Ying; Platzbecker, Uwe; Steensma, David P.; Wolff, Johannes E.; Fenaux, Pierre
Highlights: Survival rates reported among HR-MDS patients are inconsistent across clinical studies. Real-world OS with azacitidine is consistently shorter compared to that observed in the large pivotal trial AZA-001. We investigated surrogate endpoints for patients with HR-MDS treated with azacitidine. This systematic review determined clinical benchmarks for future studies of HMA-based combinations. Benchmarks of response from 237 clinical studies included complete remission (CR) rate, marrow CR, and overall survival. Abstract: The hypomethylating agent azacitidine can prolong overall survival (OS) in patients with higher risk-myelodysplastic syndromes (HR-MDS) compared to conventional regimens. However, outcomes differ largely between studies, making it challenging to determine the contribution of novel therapies added to azacitidine. Further, a discrepancy is seen between complete (CR) or partial (PR) response rates and OS improvement with azacitidine, making it challenging to rely on earlier endpoints than OS. We conducted a systematic literature search and study-level systematic review of 237 clinical studies to better understand outcomes for HR-MDS patients treated with azacitidine. Pooled marrow CR was 9% (N = 2654; 95% CI: 6–13 %), CR rate was 17 % (N = 6943; 95% CI: 15–20 %), and median OS (mOS) was 18.6 months (N = 2820; 95% CI: 15.3–21.9). A weak correlation to mOS was detected with CR rate (207 patient cohorts, Pearson's r = 0.315; P < 0.0005), and a much stronger correlation with median progression-free survival (mPFS) (r=0.88, P = 3 × 10 −14 ). Six-months progression-free survival rates correlated with 1-year OS rates but were only infrequently reported (N = 41 patient cohorts) therefore not allowing a robust recommendation for a surrogate to the established OS endpoint. Larger patient numbers and patient-level data appear necessary, especially for designing future clinical trials using azacitidine combinations.